Exogenous Ketone Salt Supplementation and Whole-Body Cooling Do Not Improve Short-Term Physical Performance - Clark, Daniel; Munten, Stephanie; Herzig, Karl-Heinz; Gagnon, Dominique D. (Frontiers in Nutrition, 2021)
Exogenous ketone supplementation and whole-body cooling (WBC) have shown to independently influence exercise metabolism. Whether readily available ketone salts, with and without WBC, would provide similar metabolic benefits during steady-state aerobic and time-trial performances was investigated. Nine active males (V̇O2peak: 56.3 ± 2.2 mL·kg-1·min-1) completed three single-blind exercise sessions preceded by: 1) ingestion of placebo (CON), 2) ketone supplementation (0.3g·kg-1 β-OHB) (KET), and 3) ketone supplementation with WBC (KETCO). Participants cycled in steady-state (SS, 60% Wmax) condition for 30-min, immediately followed by a 15-min time trial (TT). Skin and core temperature, cardio-metabolic and respiratory measures were collected continuously, whereas venous blood samples were collected before and after supplementation, after SS and TT. Venous β-OHB was elevated, while blood glucose was lower, with supplementation vs. CON (p<0.05). TT power output was not different between conditions (p=0.112, CON: 190 ± 43.5 W, KET: 185 ± 40.4 W, KETCO: 211 ± 50.7 W). RER was higher during KETCO (0.97 ± 0.09) compared to both CON (0.88 ± 0.04, p=0.012) and KET (0.88 ± 0.05, p=0.014). Ketone salt supplementation and WBC prior to short-term exercise sufficiently increase blood β–OHB concentrations, but do not benefit metabolic shifts in fuel utilization or improve time trial performance.